Characterization of dentatin isolated from Clausena excavate and its potential use for treatment of human breast and prostate cancers - Ishag, Ismail Adam Arbab (2012)
To date, there has been no literature reported on the mechanism of dentatin and its effects on breast and prostate cancers. Hence, anti-cancer effect of dentatin was investigated towards breast (in vivo and in vitro) and prostate (in vitro) cancers. Ethnopharmacologically, Clausena excavata Burm. F., has been used as folk medicines in the eastern of Thailand for the treatment of cancer. Dentatin (DTN) was isolated from this plant via bio assay guided approach and its apoptosis mechanism was investigated. With respect to MCF-7 cells of breast, DTN induced cytotoxicity was observed using MTT assay. Acridine orange/Propidium iodide staining was used to detect the early apoptosis cells. High content screening (HCS) was used to observe the nuclear condensation,cell permeability, mitochondrial membrane potential (MMP) and cytochrome c release. Apoptosis was confirmed by using clonogenic assay, DNA laddering and caspase 3/7 and 9 assays. Reactive oxygen species formation, Bcl-2/Bax expressions and cell cycle arrest also has been investigated. The involvement of NF-kB was analyzed using HCS assay. Significant increase in chromatin condensation in the cell nucleus was observed in the fluorescent analysis. The apoptosis was confirmed by reduced colony of cells in clonogenic assay and increased cellular DNA breaks on treated cells observed as ladder. Treatment of MCF-7 cells with DTN encouraged apoptosis with cell death-transducing signals that reduced the MMP by down-regulation of Bcl-2 and up-regulation of Bax, triggering the cytochrome c release from mitochondria to cytosol. The released cytochrome c triggered the activation of caspase 9 and then the executioner caspase 3/7. The DTN treatment significantly arrested MCF-7 cells at G0/G1 phase (p < 0.05). The ROS was significantly found to be elevated. Moreover the DTN significantly blocks the induced translocation of NF-kB from cytoplasm to nucleus. This part of the study was set to investigate anti-proliferative potential of dentatin (a natural coumarin isolated from Clausena excavata Burm.F) against prostate cancer and to delineate the underlying mechanism of action. Treatment with dentatin dose-dependently inhibited cell growth of PC-3 and LNCaP prostate cancer cell lines, whereas it showed less cytotoxic effects on normal prostate epithelial cell line (RWPE-1). The inhibitory effect of dentatin on prostate cancer cell growth was due to induction of apoptosis as evidenced by Annexin V staining and cell shrinkage. We found that dentatin mediated accumulation of reactive oxygen species (ROS) and downregulated expression levels of anti-apoptotic molecules (Bcl-2, Bcl-xL and Survivin), leading to disruption of mitochondrial membrane potential (MMP), cell membrane permeability and release of cytochrome c from the mitochondria into the cytosol. These effects were associated with induction of caspase-9,-3/7activities and subsequent DNA fragmentation. In addition, we found that dentatin inhibited TNF-α-induced nuclear translocation of p65, suggesting dentatin as a potential NF-κB inhibitor. Acute toxicity tests by intraperitoneal administration of up to 1 g/kg in rats did not show any biochemical, anatomical, or histopathological signs of toxicity, suggesting dentatin is relatively tolerable in vivo. An in vivo study was conducted to determine the effect of dentatin (DTN) on LA-7 cell-induced rat mammary tumor. In this study, we evaluated for the first time the anti-tumor potential of dentatin (30mg/kg LD and 60 mg/kg HD body weight), orally administered for four weeks against LA7-induced mammary carcinogenesis in SD rats. After the first tumors appearance, the thirty rats were divided into five groups (n=6). The first group comprised untreated normal healthy rats and served as the normal negative control group (NNC), while the second group comprised rats induced to develop mammary gland tumor and served as the positive control. This group of rats received a single dose of 1 ml of soy oil and was ascribed as mammary tumor control (MTC). The third group of mammary gland tumor-bearing rats was treated weekly with 30/kg mg (low dose) DTN dissolved in 1 mL soy oil. As a result, this group was assigned the group DTN-LD. The fourth group also comprised the mammary gland tumor-bearing rats and each rat received 60 mg/kg (high dose) DTN dissolved in 1 mL soy oil and assigned the group DTN-HD. Also, the fifth group comprised rats with mammary gland tumor that treated with 10 mg/kg TAM dissolved in 1 mL soy oil and assigned as the TAM group. The results suggest that DTN has better effect on the tumor compared to TAM, which promoted apoptosis in the rat mammary gland tumor. However, the DTN-HD showed a more prolonged effect suggesting that DTN could be a vital future drug in the chemotherapy of breast cancers. Hence, further studies are warranted to further investigate and develop a drug delivery system for DTN in the treatment of cancers. Together, results presented in this study demonstrated that the DTN inhibited the proliferation of MCF-7, PC-3 and LNCaP cells, leading to the cell cycle arrest and programmed cell death, which was confirmed to be through the mitochondrial pathway with the involvement of NF-kB signaling pathway. The in vivo study suggests that DTN reduced oxidative stress, inhibited proliferation, induced mitochondria-regulated apoptosis, therefore, minimizing LA-7-induced carcinogenesis in rat mammary glands. Thus, we suggest that dentatin may have therapeutic value in breast and prostate cancer treatment worthy of further development.